Aging alters the metabolic flux signature of the ER‐unfolded protein response in vivo in mice. Issue 3 (16th February 2022) - Ward, Catherine P.; Peng, Lucy; Yuen, Samuel; Halstead, John; Palacios, Hector; Nyangau, Edna; Mohammed, Hussein; Ziari, Naveed; Dandan, Mohamad; Frakes, Ashley E.; Gildea, Holly K.; Dillin, Andrew; et al.
Abstract: Age is a risk factor for numerous diseases, including neurodegenerative diseases, cancers, and diabetes. Loss of protein homeostasis is a central hallmark of aging. Activation of the endoplasmic reticulum unfolded protein response (UPR ER ) includes changes in protein translation and membrane lipid synthesis. Using stable isotope labeling, a flux "signature" of the UPR ER in vivo in mouse liver was developed by inducing ER stress with tunicamycin and measuring rates of both proteome‐wide translation and de novo lipogenesis. Several changes in protein synthesis across ontologies were noted with age, including a more dramatic suppression of translation under ER stress in aged mice as compared with young mice. Binding immunoglobulin protein (BiP) synthesis rates and mRNA levels were increased more in aged than young mice. De novo lipogenesis rates decreased under ER stress conditions in aged mice, including both triglyceride and phospholipid fractions. In young mice, a significant reduction was seen only in the triglyceride fraction. These data indicate that aged mice have an exaggerated metabolic flux response to ER stress, which may indicate that aging renders the UPR ER less effective in resolving proteotoxic stress. Abstract : Exaggerated unfolded protein response ER signature in aged animals, with higher translation of ER stress‐related proteins, lower translation of all other proteins, lower rates of de novo lipogenesis, and BiP protein synthesis and mRNA abundance higher in aged animals with tunicamycin induced ER stress.